2021
DOI: 10.3389/fmed.2021.730327
|View full text |Cite
|
Sign up to set email alerts
|

Change of Retinal Vessel Density After Lowering Intraocular Pressure in Ocular Hypertension

Abstract: Purpose: To investigate the relationship between retinal microvasculature changes and intraocular pressure (IOP) for ocular hypertension (OHT) patients and further assess the factors associated with retinal microcirculation changes.Methods: This was a single-center prospective study designed for OHT patients, which consisted of two visits. After collecting baseline data of those who met the eligibility criteria, these patients were treated with latanoprost 0.005% ophthalmic solution for 4 weeks. Peripapillary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
(115 reference statements)
0
3
1
Order By: Relevance
“…However, the effect of the IOP on VD outcomes is unclear. Although Chen et al 37 reported that, in patients with ocular hypertension, a reduction in IOP by 6.5 mmHg could led to an 1.2% increase in peripapillary VD, the IOP difference was smaller (2.0 mmHg) in our study and the VD difference was larger (3.5%). The multivariate analysis also did not reveal a significant effect of IOP.…”
Section: Discussioncontrasting
confidence: 89%
“…However, the effect of the IOP on VD outcomes is unclear. Although Chen et al 37 reported that, in patients with ocular hypertension, a reduction in IOP by 6.5 mmHg could led to an 1.2% increase in peripapillary VD, the IOP difference was smaller (2.0 mmHg) in our study and the VD difference was larger (3.5%). The multivariate analysis also did not reveal a significant effect of IOP.…”
Section: Discussioncontrasting
confidence: 89%
“…IOP is a major risk factor for the development of glaucoma and its progression (9,10). After an increase in IOP, the ganglion cells of the retina are altered, which is demonstrated by studies of different animal models of glaucoma revealing a higher sensitivity (compared with other parvocellular ganglion cells) to IOP in magnocellular ganglion cells (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al ( 9 ) previously investigated the effect of latanoprost (a drug that lowers IOP) on VD. This study found statistically significant increases of VD in the IT, TS, ST, SN, NI and IN segments.…”
Section: Discussionmentioning
confidence: 99%
“…This result could be partially explained by the IOP-induced deterioration of blood flow autoregulation. Chen et al 23 reported that the peripapillary VD of ocular hypertension patients increased after IOP reduction. Choi et al 24 found a decrease in VD around the optic nerve head in the vitrectomized eyes of pigs with high IOP.…”
Section: Discussionmentioning
confidence: 99%